Dane Rudhyar: His music, thought, and art - Ertan, Deniz (Rochester University of Rochester Press, 2009)
Dane Rudhyar (1895-1985) was a unique figure in twentieth-century American culture: a composer, thinker, painter, poet, novelist, and expert on astrology. His thought and work transcended disciplinary boundaries, integrating perspectives that were, and often still are, generally pursued in isolation from each other.Rudhyar's musical compositions -- such as the remarkable Three Paeans for piano -- were often described at the time as ultramodern and deeply philosophical. Noted music critic Nicolas Slonimsky described Rudhyar's music as "searching and challenging . . . the explanation of a puzzle of human existence."Rudhyar's sometimes startling paintings and his brilliantly articulate prose writings on a variety of subjects reached outward to pre-Renaissance and non-Western traditions. Novelist Henry Miller praised Rudhyar's ability "to show the relation between the parts, and finally to relate the parts to the whole. . . . He is so many things precisely because his sight is always focused on the central core, on the source from which all flows."Dane Rudhyar: His Music, Thought, and Art is the first full-length study of this remarkable polymath and citizen of the world and universe. The book is enriched with numerous color illustrations of Rudhyar's paintings and with examples drawn from his music and writings.Deniz Ertan has taught at the Universities of Manchester and Nottingham.